The importance of heat against antinutritional factors from Chenopodium quinoa seeds - Silva, José Antonio da (2015)
Chenopodium quinoa seeds have high protein content. The nutritional value of quinoa is superior compared with traditional cereals. Its essential amino acid composition is considered next to the ideal, and its quality matches that of milk proteins. In this study, the seed storage proteins from Chenopodium quinoa were extracted, fractionated, partially purified, and characterized. The structural characterization was performed by Tricine-SDS-PAGE and two-dimensional electrophoresis, and it confirmed the presence of proteins of molecular weight of 30 and 7kDa, probably corresponding to lectins and trypsin inhibitors, respectively. The functional characterization of these proteins evidenced their activity as antinutritional factors due to their in vitro digestibility. Quinoa proteins have an excellent amino acid composition with many essential amino acids. In vitro digestibility evaluation indicated that heat-treated samples showed a more complete digestion than the native state samples. Quinoa seeds can be an important cereal in human diet after adequate heat treatment.